Results of a comparative analysis of magnetic resonance imaging-targeted versus three-dimensional transrectal ultrasound prostate biopsies: Size does matter. (3rd May 2016) - Peltier, Alexandre; Aoun, Fouad; Albisinni, Simone; Marcelis, Quentin; Ledinh, Dam; Paesmans, Marianne; Lemort, Marc; van Velthoven, Roland
Abstract: Objective . The aim of this study was to compare the detection rate of clinically significant disease in magnetic resonance imaging (MRI)-targeted biopsies versus three-dimensional transrectal ultrasound (3D TRUS)-guided biopsies according to prostate size. Methods . The study compared 120 consecutive biopsy-naïve men who underwent 3D TRUS-guided systematic biopsy to 120 consecutive men who underwent MRI-targeted biopsy. Stratifications based on tertiles were used for assessing interactions between prostate volume and rates of detection of significant cancer. Results . Older age, higher prostate-specific antigen level, lower prostate volume, increased number of cores and MRI-targeted biopsy were independent predictors of prostate cancer detection in the entire cohort on logistic regression. Clinically significant cancer detection rates were significantly higher in the MRI-targeted group than in the 3D TRUS-guided biopsy group (48.7% vs 29.4%, p = 0.002). When stratified according to prostate volume, these rates were significantly higher only in the third tertile group (volume > 50 cm 3 ) for MRI-targeted biopsy compared to 3D TRUS-guided biopsy (56% vs 22%, p = 0.003). Conclusion . MRI-targeted biopsies increased the detection rate of clinically significant prostate cancer only in patients with enlarged prostates compared to the 3D TRUS.